Measurement and evaluation practices in academic libraries and their contributions towards strategic planning / Wan Nor Haliza Wan Mokhtar - Wan Mokhtar, Wan Nor Haliza (Institute of Graduate Studies, UiTM, 2018)
Measurement and evaluation is one of the most important elements of the library management. Measurement and evaluation practices at the library are needed in fulfilling users' satisfactions by providing good library facilities and services to the users. All libraries aim to ensure that excellent services are provided to meet users' needs and expectations. Nevertheless, to ensure the needs of users are fulfilled is not an easy job and can't be taken lightly too. A big batch of things should be remarked that the purpose and objective of the library to supply the best service to users can be employed. This work is centred on the measurement and evaluation at the academic libraries in Malaysia. The purpose of this study is to find the actual situation of measurement and evaluation practices in eight Malaysian Academic Libraries and the contributions in the library strategic planning. The findings generated from this survey provide the measurement and evaluation scenario of how academic libraries are trying to satisfy the demands and satisfactions of their users. The study which focuses on the measurement and evaluation practices of users' needs and expectations in Malaysian academic libraries highlights how libraries establish their measurement and evaluation exercises. This study, which includes the perspectives of librarians who are directly involved in the measurement and evaluation activities in the academic library may serve as a baseline in a general sense for academic libraries of all sizes as to how academic libraries could leverage the ideas of fulfilling the needs and expectations of the users…